THE STUDENTS’ PERCEPTION TOWARDS GOOGLE TRANSLATE AS A SUPPORTING MEDIA TO LEARN ENGLISH - Lestari, Lusiana Indah; Nurcahyo, Agung Dwi; Romadlon, Farid Noor (Universitas Muria Kudus, 2023)
Now, with the sophistication of smartphones, students can use Google to find out what is not known anywhere and anytime. One of the searches that students often use in learning English is Google Translate. Google Translate is a free multilingual translation service developed by Google which is used to translate text from one language to another. The students always open Google Translate many times when they don't know the meaning of a word, sentence, and text. The objective of the research was to describe the twelfth grade students' perception towards Google Translate as a supporting media to learn English at SMK Al-Hikmah Mayong. The researcher used descriptive qualitative research and the data was collected by the use of a questionnaire. In this research, the researcher used descriptive qualitative research. The participants were students of XII TAV 1 and XII TAV 2 of SMK Al-Hikmah Mayong which consist of 50 students. The result showed that the students of twelfth grade of SMK Al-Hikmah Mayong had a positive perception towards Google Translate as a supporting media to learn English with the majority of the answers they chose being “agree” that it helped them in learning English. They used Google Translate to help them such as to translate, check pronunciation, spell the word, and check synonyms. However, the results of the text translation from Google Translate are less accurate. It has a much different meaning than the original meaning.